A case of broad ligament leiomyoma presenting as an ovarian mass - Kumari, Rajesh; Vaishya, Vandana; Kulshrestha, Vidushi; Sharma, Jai Bhagwan; Kriplani, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The broad ligament is the commonest extra uterine site for the occurrence of leiomyoma but with a very low incidence rate. It poses both clinical and radiological challenge in differentiating from an ovarian tumour. A 25-year-old unmarried female presented with history of lower abdominal pain associated with rapidly increasing abdominal distension for last 3 months. General physical examination was unremarkable. Examination of the abdomen revealed a firm, non-tender mass, with limited mobility arising from the pelvis corresponding to a uterine size of 32 weeks. Ultrasonography of abdomen revealed a 20×17×11cm right adnexal multi-loculated cyst. Contrast enhanced computer tomography scan of abdomen and pelvis showed a 12×17×17 cm well defined cystic lesion arising from the pelvis and ascending in to the abdominal cavity. The lesion also showed internal septa and peripheral rim enhancement. Right ovary was not seen separately. Tumor markers including CA-125 (22.4 IU/ ml), CEA (1.83/ml), CA-19.9 (22U/ml), Beta HCG (1.20IU/ ml), LDH (1.17IU/ml), and alpha feto-protein (0.8 ng/ml) were within normal limit. Laparotomy revealed a cystic mass arising from the right broad ligament. Histopathological examination revealed a broad ligament leiomyoma with extensive cystic degeneration. Broad ligament leiomyoma is uncommon tumour of pelvis and its differentiation from ovarian masses may be challenging for the clinicians.